Safety and immunogenicity of the Na-APR-1 hookworm vaccine in infection-naïve adults. Issue 42 (6th October 2022) - Diemert, David J.; Zumer, Maria; Campbell, Doreen; Grahek, Shannon; Li, Guangzhao; Peng, Jin; Elena Bottazzi, Maria; Hotez, Peter; Bethony, Jeffrey
Abstract: Background: The Necator americanus hemoglobinase, aspartic protease-1 ( Na -APR-1), facilitates the ability of adult hookworms to parasitize the intestine of their human hosts. A recombinant version of APR-1 protected laboratory animals against hookworm infection by inducing neutralizing antibodies that block the protein's enzymatic activity and thereby impair blood feeding. A catalytically inactive version of the wild-type hemoglobinase ( Na -APR-1(M74)) was expressed by infiltrating Nicotiana benthamiana tobacco plants with an Agrobacterium tumefaciens strain engineered to express the vaccine antigen, which was adjuvanted with aluminum hydroxide adjuvant (Alhydrogel). Methods: An open-label dose-escalation Phase 1 clinical trial was conducted in 40 healthy, hookworm-naïve adult volunteers in the United States. Participants received 30 or 100 µg of recombinant Na -APR-1(M74) with Alhydrogel or with Alhydrogel co-administered with one of two doses (2.5 or 5.0 µg) of an aqueous formulation of Glucopyranosyl Lipid A (GLA-AF). Intramuscular injections of study vaccine were administered on days 0, 56, and 112. Results: Na -APR-1(M74)/Alhydrogel was well-tolerated; the most frequent adverse events were mild or moderate injection site tenderness and pain, and mild or moderate nausea and headache. No serious adverse events or adverse events of special interest related to vaccination were observed. Significantly higher levels of antigen-specific IgG antibodies were induced in those who received 100 µg Na -APR-1(M74) than those who received 30 µg of antigen. Adding GLA-AF to Na -APR-1(M74)/Alhydrogel resulted in higher levels of IgG against Na -APR-1(M74) in both the 30 and 100 µg Na -APR-1(M74) groups in comparison to the non-GLA formulations at the same antigen dose. Conclusions: Vaccination of hookworm-naïve adults with recombinant Na -APR-1(M74) was well-tolerated, safe, and induced significant IgG responses against the vaccine antigen Na -APR-1(M74). Given these favorable results, clinical trials of this product were initiated in hookworm-endemic areas of Gabon and Brazil.